Analysis of Rice Production Scale in Kerambitan Sub-District, Tabanan Regency - Ni Putu Ayu Sintami Dewi; Luh Gede Meydianawathi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Agriculture is a sector that plays a vital role in the economies of many developing countries, including Indonesia. This study aims to analyze the production scale and examine the factors influencing rice production, such as capital, labor, and land area. The research was conducted in Kerambitan Sub-district, Tabanan Regency. The agricultural sector, particularly rice production, plays an essential role in the regional economy and food security. However, it continues to face fluctuations due to various influencing factors. This study employs a quantitative method using multiple linear regression based on the Cobb-Douglas production function to measure the scale of production. Data were collected through questionnaires and interviews with rice farmers in Kerambitan Sub-district, using proportionate stratified random sampling. The results indicate that capital, labor, and land area have a positive and significant effect on rice production in Kerambitan Sub-district, Tabanan Regency. Furthermore, the production scale in this study shows decreasing returns to scale, meaning that each additional unit of input yields a proportionally smaller increase in output. These findings imply the need for strategies to enhance production efficiency and optimize resource utilization to improve rice productivity.